Knowledge Needs and Seeking Processes of Librarians of Academic Institutions in Ghana - Issah, Dawuda; Hardi, Abdul Rahim M.; Wumbie, Bawa Abdul-Majeed; Plahar, Joseph Dotse Komla (Ghana Library Journal, 2024)
This research study delves into the knowledge needs and seeking processes of librarians within the academicinstitutions of Ghana. The primary objectives of this investigation were to identify the knowledge needs of library staff, scrutinize the knowledge seeking processes employed by librarians, and uncover the challenges hindering librarians’ knowledge acquisition. A quantitative research methodology was employed to gather and analyze data, providing valuable insights into the knowledge dynamics within the Ghanaian academic library community. The findings of this study unveiled that the knowledge needs of library staff are primarily centered around two key areas: professional development within the library field and the acquisition of information and communication technology (ICT) skills, as well as research skills. These knowledge needs reflect the evolvingroles of librarians as they adapt to the digital age and strive to provide enhanced services to their academiccommunities. Regarding the knowledge seeking processes adopted by librarians, the research revealed a multifaceted approach. Librarians actively pursue knowledge through strategies such as attending workshops,seeking advice from experienced colleagues, engaging in reading materials, and watching instructional videos. Additionally, many librarians choose to pursue further studies to deepen their expertise, indicating a commitment to continuous learning and professional growth. However, the study also brought to light severalchallenges faced by librarians in their knowledge seeking endeavors. Notable challenges included financialconstraints, which hindered access to training opportunities, as well as a lack of motivation among some library staff. Furthermore, the absence of structured Knowledge Management (KM) policies within academic institutions was identified as a substantial impediment to effective knowledge sharing and utilisation. In light of these findings, it was recommended that the management of academic institutions in Ghana take proactive measures to address these challenges. To enhance the knowledge and skills of library staff, appropriate training programmemes should be developed and made readily available. Furthermore, the establishment of comprehensive KM policies is essential to guide and facilitate the knowledge activities within libraries, fosteringa culture of continuous learning and knowledge sharing